An investigation of the effects of laser-assisted zona pellucida drilling on the preimplantation mouse embryo and the competency of embryo implantation - Coward, K; Jones, C; Liu, Y (Elsevier, 2021)
Objective: To investigate the impact of laser-assisted zona pellucida (ZP) drilling on the mouse embryo, with particular emphasis on molecular mechanisms, and the efficiency of embryo attachment capability using an in vitro model of implantation.